#TITLE_ALTERNATIVE# - KUNCORO AJI (NIM : 20212023); Pembimbing : Dr. Abdul Waris, INDARTA
The neutron kinetics of the Molten Salt Reactor is influenced by the flow rate of the fuel. This research analyzed flow rate changes by the molten salt fuel at MSR Fuji-12 with composition LiF-BeF2-ThF4-233UF4 respectively 71.78%- 16%-11.86%-0.36% Calculation process in this study is performed numerically by SOR and finite difference methode, as well as using the C programing language. Data of reactivity, neutron flux, and the macroscopic fission cross section are used were obtained from the calculation of SRAC CITATION with JENDL-4.0 data library. The results of this calculation is known that speed setting of flow rate by MSR Fuji-12 fuel salt can be used to determine the level of criticalty of the reactor when operate at the first year until the fifth year.